Philosopher Michel Foucault's Ideation and Indonesia's Curricular Quest - Alfonso Munte; Yoga Saputra; Xie Guilin (Journal Neosantara Hybrid Learning, 2023)
Manku Tosok Private Primary School is categorized as one of the schools in the frontier, remote and disadvantaged areas based on the narrative of various research subjects. As consequences, researchers witnessed the diversity of challenges and opportunities during the learning process, both during the Covid-19 pandemic and post-Covid-19. Based on those situations, researchers unraveled how the inherent problems of implementing the K13 curriculum and its impulses today (post Covid-19), Central Kalimantan based on various narratives presented by teachers and school principals. The qualitative method involved collecting data through in-depth interviews with three interviewees to express their arguments or experiences as teachers while encountering various situations in rural areas. The interview audio recordings were transcribed into verbatim transcripts, solidified into factual solids, and the researchers created themes to narrow down issues discussed during the research discussion section. Based on the findings showed that teachers and principals were willing to provide solutions to students by visiting them one by one, although eventually, due to the limitations of teachers and time, teachers and school principals provided alternative learning through limited in-person meetings pursuant to school policies.